Diurnal Variation in the Photosynthetic Traits of Sclerocarya birrea (Marula) Trees in North Namibia - Amuthenu, Ndapandula; Huttunen, Sanna; Nanhapo, Pamwenafye; Ndeinoma, Albertina; Toivonen, Johanna M. (Wiley, 2026)
Sclerocarya birrea (marula) trees are important components of dry and semi-dry African savanna environments due to their ecological and economical importance, including carbon storage. However, functional characteristics of these dioecious trees, such as their photosynthetic rates, remain largely unstudied. We quantified the diurnal cycle in leaf-level net photosynthetic rate (A), stomatal conductance (gsw) and transpiration (E) in sun and shade leaves of male and female individuals of 14 Sclerocarya birrea trees in a northern Namibian semi-arid agroforestry system and explained the observed trends by three environmental drivers (light, temperature and humidity). A generalised additive model with a thin-plate regression spline smoother was applied to describe non-linear diurnal variation in A, gsw and E. Results revealed a pronounced pre-midday decline in A for sun leaves, from 5.5 μmol CO₂ m−2 s−1 in the morning to 2.4 μmol CO₂ m−2 s−1 in the late afternoon, while shade leaves showed a continuous decrease from 3.0 to 1.8 μmol CO₂ m−2 s−1. Correspondingly, gsw declined from 0.07 to 0.04 mol m−2 s−1, and E from 0.0012 to 0.0008 mol m−2 s−1 between morning and afternoon hours for sun leaves. Male trees exhibited higher A, gsw and E than females, suggesting secondary sexual dimorphism in gas-exchange traits. Light was the best predictor of net photosynthetic rate and transpiration, whereas temperature was the best predictor of stomatal conductance. These findings highlight the complex interplay between environmental factors, leaf position and tree-specific traits in shaping the photosynthetic performance of Sclerocarya birrea. Consequently, this knowledge enables better-informed management and conservation strategies for this key savanna species.